2015
DOI: 10.1111/hsc.12228
|View full text |Cite
|
Sign up to set email alerts
|

Physician perspectives on care of individuals with severe mobility impairments in primary care in Southwestern Ontario, Canada

Abstract: Despite the high health risks associated with severe mobility impairments, individuals with physical disabilities are less likely to receive the same level of primary care as able-bodied persons. This study explores family physicians' perspectives on primary care for individuals with mobility impairments to identify and better understand the challenges that prevent equitable service delivery to this group of patients. Semi-structured interviews were conducted in the autumn of 2012 with a purposeful sample of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(87 citation statements)
references
References 25 publications
2
76
0
9
Order By: Relevance
“…This was especially salient given that some family physicians did not feel it was their role to have specialized medication knowledge relating to common SCI/D secondary conditions. Previous research has identified a similar concern among primary care physicians [28,41]. McMillan and colleagues identified that while physicians acknowledge important knowledge gaps and the need for additional general education about providing care for persons with mobility issues, the lack of time and substantial effort required were barriers [41].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This was especially salient given that some family physicians did not feel it was their role to have specialized medication knowledge relating to common SCI/D secondary conditions. Previous research has identified a similar concern among primary care physicians [28,41]. McMillan and colleagues identified that while physicians acknowledge important knowledge gaps and the need for additional general education about providing care for persons with mobility issues, the lack of time and substantial effort required were barriers [41].…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has identified a similar concern among primary care physicians [28,41]. McMillan and colleagues identified that while physicians acknowledge important knowledge gaps and the need for additional general education about providing care for persons with mobility issues, the lack of time and substantial effort required were barriers [41]. To address some of these barriers, enhancing interprofessional collaborations between pharmacists and physicians may provide more clinical support for complex MTM.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons include lack of transportation, wheelchair ramps, inadequate space for mobility aids, and inability to transfer to an examination table. [1][2][3][4][5] Accessibility is a critical step to ensuring persons with SCI can obtain the care they need. Some government legislation such as the Accessibility for Ontarians with Disabilities Act (2005), mandate that all medical practices be fully accessible in the future.…”
Section: The Problemmentioning
confidence: 99%
“…While this may ensure that medical practices are physically accessible by wheelchair, patients may still find their care compromised by the lack of appropriate medical equipment such as height-adjustable examination tables, transfer mechanisms such as ceiling lifts, and grab bars. 6 In a recent study we conducted, 3 family physicians reported that without appropriate medical equipment they are unable to properly examine patients resulting in a focus on episodic or acute care rather than preventive care. In some reported cases, patients have been sent to the Emergency Department for care solely due to accessibility and equipment issues.…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation